Organ Donation in China. (August 2017) - Matas, David
Abstract : Introduction: The Government of China introduced a donation system for organs long after it had developed a nation-wide, high volume organ transplantation industry. The Government has acknowledged that, before its donation system was introduced, the bulk of organs for transplants was coming from prisoners. The Government says that donors have replaced prisoners as sources for organs. The purpose of this presentation would be first to assess this assertion. The second purpose would be to consider the implications of this assessment. Methods: In assessing the assertion that sourcing in China of organs for transplants come from voluntary donors, the presentation would consider the statements of Chinese health officials about transplant volumes and sources, the results of investigations into volumes at individual donation centres, transplant volumes in individual hospitals, the current law in China about organ sourcing, and information about payments to families for organ donation. Results: Donation volumes do not account for transplant volumes. Statements by health officials have been inconsistent. The law which allows sourcing of organs from prisoners remains in force. The numbers which individual donation centres are generating is tiny. It is impossible to account for transplant volumes through the numbers being generated from donation centres. This is true even if one takes into account purchased organs. Conclusion: Donations cannot account for transplant volumes in China. Organ sourcing from prisoners in China continues. There are these implications: Both the European Union Parliament and the United States Congress House of Representatives have called by way of resolution for an independent investigation into the sourcing of organs for transplantation in China. This call for an independent investigation remains as valid as ever. Health professionals abroad should not collaborate in research with health professionals in China on transplantation unless the sourcing of organs for research is proper beyond a reasonable doubt. No journal should publish transplant research from any researcher in China unless the sourcing of organs for research which is being written up is proper beyond a reasonable doubt. No conference should allow presentation of transplantation research done in China unless the sourcing of organs for research which is being presented up is proper beyond a reasonable doubt. References: 1. David Matas and David Kilgour "Bloody Harvest". 2. Ethan Gutmann "The Slaughter". 3. David Matas, David Kilgour and Ethan Gutmann "An update to Bloody Harvest and The Slaughter".